Homocysteine Causes Endothelial Dysfunction via Inflammatory Factor-Mediated Activation of Epithelial Sodium Channel (ENaC) - Liang, Chen; Wang, Qiu-Shi; Yang, Xu; Zhu, Di; Sun, Yu; Niu, Na; Yao, Jie; Dong, Bi-Han; Jiang, Shuai; Tang, Liang-Liang; Lou, Jie; Yu, Chang-Jiang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Hyperhomocysteinemia (HHcy) causes cardiovascular diseases via regulating inflammatory responses. We investigated whether and how the epithelial sodium channel (ENaC), a recently identified ion channel in endothelial cells, plays a role in HHcy-induced endothelial dysfunction. Methods: Cell-attached patch-clamp recording in acute split-open aortic endothelial cells, western blot, confocal imaging, and wire myograph combined with pharmacological approaches were used to determine whether HHcy-mediated inflammatory signaling leads to endothelial dysfunction via stimulating ENaC. Results: The data showed that four weeks after L-methionine diet the levels of plasma Hcy were significantly increased and the ENaC was dramatically activated in mouse aortic endothelial cells. Administration of benzamil, a specific ENaC blocker, ameliorated L-methionine diet-induced impairment of endothelium-dependent relaxation (EDR) and reversed Hcy-induced increase in ENaC activity. Pharmacological inhibition of NADPH oxidase, reactive oxygen species (ROS), cyclooxygenase-2 (COX-2)/thromboxane B2 (TXB2), or serum/glucocorticoid regulated kinase 1 (SGK1) effectively attenuated both the Hcy-induced activation of endothelial ENaC and impairment of EDR. Our in vitro data showed that both NADPH oxidase inhibitor and an ROS scavenger reversed Hcy-induced increase in COX-2 expression in human umbilical vein endothelial cells (HUVECs). Moreover, Hcy-induced increase in expression levels of SGK-1, phosphorylated-SGK-1, and phosphorylated neural precursor cell-expressed developmentally down-regulated protein 4-2 (p-Nedd4-2) in HUVECs were significantly blunted by a COX-2 inhibitor. Conclusion: We show that Hcy activates endothelial ENaC and subsequently impairs EDR of mouse aorta, via ROS/COX2-dependent activation of SGK-1/Nedd4-2 signaling. Our study provides a rational that blockade of the endothelial ENaC could be potential method to prevent and/or to treat Hcy-induced cardiovascular disease.